Static Stretch Increases the Pro-Inflammatory Response of Rat Type 2 Alveolar Epithelial Cells to Dynamic Stretch - Ferreira, Jorge M. C.; Huhle, Robert; Müller, Sabine; Schnabel, Christian; Mehner, Mirko; Koch, Thea; Gama de Abreu, Marcelo (Frontiers in Physiology, 2022)
Background: Mechanical ventilation (MV) inflicts stress on the lungs, initiating or increasing lung inflammation, so-called ventilator-induced lung injury (VILI). Besides overdistention, cyclic opening-and-closing of alveoli (atelectrauma) is recognized as a potential mechanism of VILI. The dynamic stretch may be reduced by positive end-expiratory pressure (PEEP), which in turn increases the static stretch. We investigated whether static stretch modulates the inflammatory response of rat type 2 alveolar epithelial cells (AECs) at different levels of dynamic stretch and hypothesized that static stretch increases pro-inflammatory response of AECs at given dynamic stretch. Methods: AECs, stimulated and not stimulated with lipopolysaccharide (LPS), were subjected to combinations of static (10, 20, and 30%) and dynamic stretch (15, 20, and 30%), for 1 and 4 h. Non-stretched AECs served as control. The gene expression and secreted protein levels of interleukin-6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), and macrophage inflammatory protein 2 (MIP-2) were studied by real-time polymerase chain reaction (RT-qPCR) and enzyme-linked immunosorbent assay (ELISA), respectively. The effects of static and dynamic stretch were assessed by two-factorial ANOVA with planned effects post-hoc comparison according to Šidák. Statistical significance was considered for p < 0.05. Results: In LPS-stimulated, but not in non-stimulated rat type 2 AECs, compared to non-stretched cells: 1) dynamic stretch increased the expression of amphiregulin (AREG) (p < 0.05), MCP-1 (p < 0.001), and MIP-2 (<0.05), respectively, as well as the protein secretion of IL-6 (p < 0.001) and MCP-1 (p < 0.05); 2) static stretch increased the gene expression of MCP-1 (p < 0.001) and MIP-2, but not AREG, and resulted in higher secretion of IL-6 (p < 0.001), but not MCP-1, while MIP-2 was not detectable in the medium. Conclusion: In rat type 2 AECs stimulated with LPS, static stretch increased the pro-inflammatory response to dynamic stretch, suggesting a potential pro-inflammatory effect of PEEP during mechanical ventilation at the cellular level.